Hechos punibles en el ámbito de las prácticas deportivas: a su vez, un ejemplo de la relevancia del resultado lesivo para la configuración del injusto penal = Crimes in the Context of Sports Competition : an Example of the Relevance of the Injury Result for the Configuration of the Punishable Offence - Modolell González, Juan Luis (Política criminal, 2021)
Why would a harmful act not have the same criminal relevance depending if it is committed during a sporting competition or if it takes place outside of it? On the other hand, why society reacts in similar manner when it comes to serious injuries to certain legal interests, such as the death of a person committed by another without any justification whatsoever, regardless of the setting in which the death occurs? Injuries to legal interests produced during a sporting competition should be treated, in principle, at the level of the factual elements, although it is necessary to distinguish socially appropriate cases or permitted risks, and irrelevant damages for society. Whenever in a sporting competition any damage, serious or slight, is produced as a consequence of an activity carried out within the rules governing the competition, it will be considered atypical because of the social appropriateness of the conduct. For their part, the injury to the legal right as a consequence of an infringement of the sports regulations could only be atypical according to the seriousness of such injury. With regard to the latter, the determining factor will be the magnitude of the injury itself rather than the normative disobedience.